The Voice Of The Homeland In The Melodies Of Our Ancestors - Durdonakhon Murodova; Dilfuzakhon Yusupjonova (Genius Journals, 2025)
This article interprets the melodies and folk music created by our ancestors as one of the most significant symbols of national identity. It highlights how ancient tunes embody the history, spirituality, emotions, and profound love of the people for their homeland. The study analyzes the roots of Uzbek musical heritage, the contributions of great scholars of Eastern music, the role of maqom art and folk melodies in fostering patriotism, moral education, and national pride. The article also emphasizes the importance of ancestral melodies in strengthening traditional values in the minds of youth today and explains how these melodies resonate as the vibrant voice of the homeland, influencing the spiritual worldview of future generations.
Keywords: Ancestral melody; national heritage; maqom; folk music